2018
DOI: 10.1186/s13041-018-0359-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DREAM-ATF6 interaction delays onset of cognition deficit in a mouse model of Huntington’s disease

Abstract: The transcriptional repressor DREAM (downstream regulatory element antagonist modulator) is a multifunctional neuronal calcium sensor (NCS) that controls Ca2+ and protein homeostasis through gene regulation and protein-protein interactions. Downregulation of DREAM is part of an endogenous neuroprotective mechanism that improves ATF6 (activating transcription factor 6) processing, neuronal survival in the striatum, and motor coordination in R6/2 mice, a model of Huntington’s disease (HD). Whether modulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…Outside the nucleus, DREAM interacts with presenilins to modulate calcium release from the endoplasmic reticulum (Lilliehook et al, 2002). Additionally, the role of the downregulation of DREAM as part of an endogenous neuroprotective mechanism that improves ATF6 processing, neuronal survival in the striatum, and motor coordination in R6/2 mice, a model of Huntington’s disease (HD), has been recently described (Naranjo et al, 2016; López-Hurtado et al, 2018). Besides, DREAM acts as a regulatory subunit of K V 4.3 channels by inducing: (i) increased traffic of K V 4.3 channels to the membrane; (ii) delayed inactivation kinetics; and (iii) accelerated activation and recovery kinetics from inactivation of K V 4.3 channels (An et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Outside the nucleus, DREAM interacts with presenilins to modulate calcium release from the endoplasmic reticulum (Lilliehook et al, 2002). Additionally, the role of the downregulation of DREAM as part of an endogenous neuroprotective mechanism that improves ATF6 processing, neuronal survival in the striatum, and motor coordination in R6/2 mice, a model of Huntington’s disease (HD), has been recently described (Naranjo et al, 2016; López-Hurtado et al, 2018). Besides, DREAM acts as a regulatory subunit of K V 4.3 channels by inducing: (i) increased traffic of K V 4.3 channels to the membrane; (ii) delayed inactivation kinetics; and (iii) accelerated activation and recovery kinetics from inactivation of K V 4.3 channels (An et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These results confirm the Ca 2+ -independent nature of this interaction, as previously described (Buxbaum et al, 1998; Fedrizzi et al, 2008). Then, we proceeded to investigate a potential blockage of the DREAM-PS2 interaction by the DREAM binding molecule repaglinide, known to affect the interaction of DREAM with other proteins including Kv4 potassium channels and ATF6 (Naranjo et al, 2016; López-Hurtado et al, 2018). In vitro exposure to repaglinide significantly reduced the Myc-DREAM/Flag-Ct-PS2 coimmunoprecipitation (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we have shown that reduction in DREAM protein levels or blockade of DREAM activity, using repaglinide, activates ATF6 processing which results in a neuroprotective effect in murine models of Huntington’s disease, delaying the onset and the progression of motor and cognitive decline in these mice (Naranjo et al, 2016; López-Hurtado et al, 2018). This finding opened a new avenue toward the search for effective HD treatments.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These observations in both photoreceptors and spinal neurons, suggest that modifying ATF6 activity could be a therapeutic approach to mitigate neurodegenerative diseases. Indeed, de-repression of Atf6 in a mouse model of Huntington’s disease provides neuroprotection to both striatal and hippocampal neurons (López-Hurtado et al, 2018; Naranjo et al, 2016). Furthermore, a small molecule activator of ATF6 reduces amyloidogenic protein secretion and aggregation, providing additional justification for targeting the ATF6 pathway in neurodegenerative disease (Plate et al, 2016).…”
Section: Discussionmentioning
confidence: 99%